Coco Chanel & Igor Stravinsky [videorecording (DVD)] - Kounen, Jan, 1964-; Kounen, Jan, 1964-; Mouglalis, Anna; Mikkelsen, Mads, 1965-; Morozova, Elena, 1973- (Sony Pictures Home Entertainment, 2010)
By the 1920s, Coco Chanel has established herself in the world of fashion. After a disastrous reaction to an early production of his Rite of Spring ballet, Igor Stravinsky has become a penniless refugee living in exile. When the two are introduced, the attraction is immediate and together they embark on a passionate affair, which results in a period of great artistic achievement for both artists.